The Temporality Of Mobile Media - Frith, Jordan; Farman, Jason; Wilken, Rowan; Oppegaard, Brett; Meyer, Joseph (AoIR Selected Papers of Internet Research, 2017)
Scholarship on mobile media has largely focused on the relationship between mobile media and space. From Sarah Sharma’s perspective, the focus — possibly overemphasis — on spatial dynamics in locative and mobile media not only relies on the most simplistic analysis of the media, but also “risks aligning the field too closely with the logic of the market.” Drawing on the work of Harold Innis, she goes on to argue that such an overemphasis on the spatial dynamics of mobile and locative media plays into the centralizing characteristics of imperial powers: “Civilizations that emphasize space over time tend to be imperial powers, involved in the conquering of space at the expense of the maintenance of culture over time.” Building off Sharma’s provocations, this panel focuses on several aspects of mobile technologies where mobility and time intersect in the most fundamental of ways. As we will discuss in our talks, the dominant focus of mobile media studies has been on spatial impacts. While this research has certainly been useful to move the field forward, it has resulted in a disproportionate focus on space over time, or spatiality over temporality. Consequently, the vast majority of work on locative media—and even most of the work on voice and texting—tends to ignore the temporal impacts of mobile media adoption. This panel seeks to flip that relationship by devoting four talks to the oft-neglected interrelations between mobile media and temporality.